Legal Protection for Brand Buyers Related to the Use of Portrait Images on Trademarks That Have Been Transferred - Victoria Ellen Subagijo; Shania Shania; Effendy Pangestu; Richard Julian (Budapest International Research and Critics University, 2022)
In the era of globalization, brands play an important role in regulating the development of world trade. Brands are used in the world of commerce to differentiate one product from another. Brand owners often use self-portrait logos with the aim of letting consumers know the owner or as a sign that the product is genuine. Disputes regarding brands are common in Indonesia, one of which involves the use of a portrait of Mrs. M on the trademark used in telon oil product packaging. This happened because previously the Ny. M was transferred due to bankruptcy so that the Right to the Mark was transferred to another party. There is a portrait of Mrs. M becomes a problem because it is considered not to be an integral part of the trademark, but is a stand-alone Copyright. The transfer of rights to the mark should include all the marks on the mark because the marks on the mark have become one and cannot be separated.